Relation Between Fast Food and Preservative Consumption with Rheumatoid Arthritis Pain in A Gymnastics Group in Bandung City - Syafina, Indira Aulia; Syah, Bagas Dwi; Ainunnisa, Rista Utami; Nurlaila, Syahnaz; Fitrianingsih, Asti Dewi Rahayu (Journal of Applied Food and Nutrition, 2024)
Background: Rheumatoid arthritis is an autoimmune disease in the form of joint inflammation in adults. Based on the 2018 WHO report, it shows that there are 335 million people in the world who have rheumatism, of which 5-10% are aged 5-20 years and 20% are aged 55 years. Factors that can cause pain in rheumatoid arthritis are dietary factors, one of which is frequent consumption of fast food and preserved foods. The aim of this study was to determine the relationship of consumption of fast food and preserved foods to rheumatoid arthritis complaints in two gymnastics groups in Bandung City.Methods: This study used a cross-sectional design with a sample of 30 gymnastic ladies taken by purposive sampling. Data were analyzed using the Chi-Square test with IBM SPSS Statistic 21 software.Results: Based on the results of the analysis that has been done, there is no relationship between age, educational history, consumption of fast food and preserved food with rheumatoid arthritis complaints in the group of gymnastics ladies in Bandung City (p0,05).Conclusions: The absence of an association among age, educational history, consumption of fast food and preserved foods with rheumatoid arthritis complaints can be due to other factors outside of these factors such as genetics, gender, obesity, infectious diseases, and lack of knowledge about rheumatoid arthritis. What's more, rheumatoid arthritis is also a multifactorial disease, so we need to wisely maintain and regulate  his, her, their, etc lifestyle and food intake so that rheumatoid arthritis complaints can be minimized and do not have recurrences.